2008
DOI: 10.1017/s0016672308009865
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epistasis and QTL×environment interaction on the accumulation of seed mass of soybean (Glycine maxL. Merr.)

Abstract: The accumulation of seed mass in soybean is affected by both genotype and environment. The aim of the present study was to measure additive, epistatic and quantitative trait locus (QTL) x environment (QE) interaction effects of QTLs on the development of 100-seed weight in a population of 143 F5 derived recombinant inbred lines (RILs) developed from the cross between the soybean cultivars 'Charleston' and 'Dong Nong 594'. Broad-sense heritability of 100-seed weight from 30 days (30D) to 80D stages was 0.58, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
0
26
1
Order By: Relevance
“…There has been a number of studies in which molecular markers have been used to investigated the developmental behavior of quantitative traits (Sun et al 2006;Han et al 2008). The results of these studies indicated that seed weight, pod number, and plant height are partially regulated by both conditional and unconditional QTL.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a number of studies in which molecular markers have been used to investigated the developmental behavior of quantitative traits (Sun et al 2006;Han et al 2008). The results of these studies indicated that seed weight, pod number, and plant height are partially regulated by both conditional and unconditional QTL.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the present study was to identify both conditional and unconditional QTL underlying the development of gain in seed weight and the QTL underlying final mean seed weight in soybean. An analysis of epistatic effects in seed weight development and formation were described in a separate paper submitted to Genetics Research (Han et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This trend suggests that some genotype 9 pathotype interaction is present. We note that a genotype 9 environment interaction is not infrequent when dealing with quantitative characters, for example, the capsaicinoids content in pepper (Garcés-Claver et al 2007), the accumulation of seed mass in soybean (Han et al 2008) or the protein or sucrose contents in beans (Florez et al 2009). Moreover, Perchepied and Pitrat (2004) reported that quantitative, polygenic, racenonspecific resistance to a specialized pathogen often shows small race-specific effects, which may explain the above results.…”
Section: Discussionmentioning
confidence: 94%